Wilde, Richard (audio interview #1 of 4) - Wilde, Richard (1920 - ); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This first of four interviews was conducted in Wilde's CSULB office in the CSULB History Department. The audio quality is good, but there is some background noise as people talk as they pass by in the hall. 7/26/1978